PENGARUH PAID PROMOTE DI MEDIA SOSIAL TERHADAP KEPUTUSAN PEMBELIAN PRODUK - Samsinar; Andi Tenri Ellyana Haris; Muhammad Taufan Gunawan; Fahril Saputra (Fakultas Ekonomi dan Bisnis, 2024)
Economic growth and technological developments are affecting the business world, especially with the emergence of various social media platforms that offer promotional and marketing services. Including the clothing industry that must continue to adapt to social media trends that affect fashion preferences. One of the strategies used is paid promotion on social media. This study aims to determine the influence of paid promotions on the purchase decision of clothing products among gen-Z. The research sample was 65 respondents using the accidential sampling method. This study uses a descriptive analysis approach to understand and provide an overview of the relationship between paid promotions and purchase decisions. The results of the study show that paid promotions have a positive and significant influence on the purchase decision of clothing products among Gen-Z.